Using physiological laboratory tests and neuromuscular functions to predict extreme ultratriathlon performance - Abad, C. C. C.; Carmo, E. C.; Do Prado, D. M. L.; Reis, V.; Pereira, L.; Loturco, I.; Koehle, M. (Research Quarterly for Exercise and Sport, 2023)
Purpose: This study aims to investigate the relationship between split disciplines and overall extreme ultra-triathlon (EUT) performance and verify the relationship among physiological and neuromuscular measurements with both fractional and total EUT performance while checking which variables could predict partial and overall EUT race time.